Leader‐Follower Dynamics in Shareholder Activism - CETEMEN, DORUK; CISTERNAS, GONZALO; KOLB, AARON; VISWANATHAN, S. (Journal of Finance, 2026)
ABSTRACT We propose a theory of coordination and influence among blockholders. Privately informed activists time their trades in sequence to lower acquisition costs, prompting a strategic use of order flows: leader activists create trading gains for their followers, ultimately influencing their willingness to bear greater value‐enhancing intervention costs. Through this channel, informed trades can exhibit predictability, in sharp contrast with Kyle (1985, Econometrica 53, 1315–1335). We explain how this novel predictability shapes free‐rider problems affecting governance, and how it produces price abnormalities analogous to those documented empirically. We also uncover how private information interdependence can be a key catalyst for the mechanism studied.